IMPLIKASI DILEMATIS STATUS JANDA BAGI WANITA - Muhamad Arifin (Sekolah Tinggi Dirasat Islamiyah Imam Syafi'i Jember, 2019)
Every woman really craves to be able to live a harmonious household life until the end of her life. But for some women, that desire sometimes has to run aground for some time, and for some others it has run aground forever. Through this study, the authors want to reveal the reasons for the reasons behind the occurrence of widow status in women. Knowledge of the background of the status of widows, the authors continued by revealing the reasons for some women who preferred to maintain their status as widows. From understanding these two aspects, the author can uncover dilemma conditions and some real solutions for a widow. The hope this research can be useful for women widows who are in a dilemma, the difficulty to decide attitude.